PML and TRF2 protein expression in hereditary and sporadic colon cancer - Plevová, Pavlína; Bouchal, Jan; Bezděková, Michala; Sekowská, Martina; Křepelová, Anna; Čuřík, Romuald; Foretová, Lenka; Navrátilová, Marie; Zapletalová, Jana; Posolda, Tomáš; Kolář, Zdeněk (Neoplasma, 2007)
The PML (promyelocytic leukemia) protein is concentrated in the PML nuclear bodies. In human cell lines and tumors maintaining their telomeres by alternative lengthening (ALT), the PML protein is colocalized with TRF2 and several other proteins in the so called ALT-associated PML bodies. The aim of this study was to determine if there is any difference in PML protein expression between tumors with stable microsatellites (MSS) and those with high-frequency microsatellite instability (MSI-H), if PML protein expression might be a prognostic factor and if MSI-H tumors more frequently use alternative lengthening of telomeres measured by the presence of ALT-associated PML bodies. Eighty colorectal cancer samples (32 MSI-H and 48 MSS) and 8 human tumor cell lines (Saos-2, U2OS, DU145, LNCaP, U87, HeLa, MCF7 and T98G) were included into the study. Double-colour immunofluorescence staining was used. Downregulation of PML protein expression was found in 7 of 32 (22%) MSI-H and 11 of 48 (23%) MSS tumors (p=0.520). There was no correlation between PML expression and age, histological typing, localization of the tumor in colon, TNM classification, disease-free and overall survival. The Saos-2 and U2OS (ALT using cell lines) and the MCF7 (active telomerase) cell line were characterized by the presence of ALT-associated PML bodies; no such bodies were detected in the DU145, LNCaP, U87, HeLa and T98G cell lines (active telomerase); accumulation of TRF2 was absent or much weaker in these cell lines compared to Saos-2 or U2OS. Accumulation of the TRF2 protein was detected in 16 of 80 (20%) tumors and PML and TRF2 colocalization in 2 MSI-H tumors (6%). In conclusion, the PML protein was downregulated in approximately 20% of tumors; there was no difference between MSS and MSI-H tumors. PML protein expression does not seem to be a prognostic factor.
Keywords: senioři; financování organizované; DNA, Neoplasm; jaderné proteiny; protein TRF2; Neoplasm Proteins; senioři nad 80 let; kolorektální nádory; Nuclear Proteins; nádorové proteiny; mucinózní adenokarcinom; mikrosatelitní repetice; polymerázová řetězová reakce; Polymerase Chain Reaction; adaptorové proteiny signální transdukční; Middle Aged; Colorectal Neoplasms; mužské pohlaví; Adult; Tumor Cells, Cultured; Transcription Factors; Microsatellite Repeats; Microsatellite Instability; Neoplasms; transkripční faktory; Aged, 80 and over; homolog 2 proteinu MutS; Financing, Organized; ženské pohlaví; nádorové supresorové proteiny; Telomeric Repeat Binding Protein 2; Adaptor Proteins, Signal Transducing; Humans; Adenocarcinoma, Mucinous; mikrosatelitní nestabilita; nádory; Tumor Suppressor Proteins; DNA nádorová; telomerasa; lidé středního věku; Telomerase; Telomere; telomery; dospělí; MutS Homolog 2 Protein; Female; Aged; nádorové buňky kultivované; lidé; Male